Avaliação do comprometimento emocional e da qualidade de vida em indivíduos com psoríase atendidos no centro de referência do estado da Paraíba - Albuquerque, Roberta Espíndola de (2023)
Psoriasis is an immune-mediated disease, characterized by a broad polymorphism in clinical presentation. The psychological aspect of the disease interferes with personal and cognitive behavior. The emotional state worsens without adequate treatment, interfering in a primary or secondary way in the patient's speech, which in response may present minor psychiatric disorders, thus affecting the individual's perception of their quality of life, associated with the well-being of their mental health. The object of the study was to investigate the factors that affect the mental health and quality of life of people diagnosed with psoriasis and that reflect the patient's degree of difficulty in living with the disease. The research was developed at the Reference Center for Research, Support and Treatment of Psoriasis of the State of Paraíba (CRPATP-PB), located at the Lauro Wanderley University Hospital of UFPB. This is an exploratory observational, analytical and retrospective research with a quantitative and cross-sectional approach, using secondary data. To assess the emotional component and quality of life, scores were collected from the following validated instruments: Self Report Questionnaire Indicator (SRQ-20) and Beck Depression Scale (BDI) and Quality of Life Index (DLQI) collected in patient's outpatient records and personal data related to the clinical aspect of psoriasis vulgaris and its degree of severity and impairment of quality of life. Furthermore, an indicator that reflects the patient's degree of difficulty was evaluated using statistical models such as Weight of Evidence (WoE) and Multiple Combinatorial Analysis. As a sample, data were extracted from 126 patient records. For data processing, the R-studio software was used, which, with the use of models and data processing, made it possible to present the prevalence and to evaluate the influence of the factors presented on Quality of Life (QoL) and Severity of Psoriasis (PASI) the WoE model was applied, with the variables of gender, age group, BDI, SRQ-20, QoL, Stress and Anxiety. Finishing with the generation of a perceptual map to evaluate associations between factors and quality of life and the severity of psoriasis, which can be divided into four well-defined quadrants and which demonstrate groupings of different stages for each patient. From the perceptual map it was possible to perceive the impairment of the patient's quality of life and mental health, that their scores are above the cut-off values of the instruments and the need to propose the formulation of two new scores, the Quality of Life Index ( IQV) and the Psoriasis Severity Index (IPSO), which aim to measure both the impairment of quality of life and the severity of the disease according to the impairment of this patient's mental and physical health. The importance of this study will benefit society by collecting data that can later be used to generate statistical indicators that can serve both to understand the reality of psoriatic patients within the emotional context and the repercussions on their quality of life, and to develop public policies.